Scaling up interventions for depression in sub-Saharan Africa: lessons from Zimbabwe. (11th April 2016) - Chibanda, D.; Verhey, R.; Munetsi, E.; Rusakaniko, S.; Cowan, F.; Lund, C.
Abstract : Background: There is a dearth of information on how to scale-up evidence-based psychological interventions, particularly within the context of existing HIV programs. This paper describes a strategy for the scale-up of an intervention delivered by lay health workers (LHWs) to 60 primary health care facilities in Zimbabwe. Methods: A mixed methods approach was utilized as follows: (1) needs assessment using a semi-structured questionnaire to obtain information from nurses ( n = 48) and focus group discussions with District Health Promoters ( n = 12) to identify key priority areas; (2) skills assessment to identify core competencies and current gaps of LHWs ( n = 300) employed in the 60 clinics; (3) consultation workshops ( n = 2) with key stakeholders to determine referral pathways; and (4) in-depth interviews and consultations to determine funding mechanisms for the scale-up. Results: Five cross-cutting issues were identified as critical and needing to be addressed for a successful scale-up. These included: the lack of training in mental health, unavailability of psychiatric drugs, depleted clinical staff levels, unavailability of time for counseling, and poor and unreliable referral systems for people suffering with depression. Consensus was reached by stakeholders on supervision and support structure to address the cross-cutting issues described above and funding was successfully secured for the scale-up. Conclusion: Key requirements for success included early buy-in from key stakeholders, extensive consultation at each point of the scale-up journey, financial support both locally and externally, and a coherent sustainability plan endorsed by both government and private sectors.